Selection of dairy culture and changes of Podravec cheese acidity during production - Slavko Kirin (Mljekarstvo)
The selection and characteristics of dairy culture play a basic role in all types of cheese production process. The most important characteristic is acidification ability i.e. lactic acid formation, which regulates manufacturing and maturing conditions of cheese, thus affecting its organoleptic characteristics as well. In this work the results on control of acidity increase in Podravec cheeseproduction are presented. In the production process, a technical culture as well as identical frozen and concentrated culture, with and without auxiliary Streptococcus thermophilus for direct milk inoculation, were used. It was established that the acidity, expressed as pH value, is more intensively developed in cheeses produced with culture for direct inoculation. This was especially evident in the first phases of production i.e. before cheese salting. During salting the acidity of cheeses, in both cases, was almoust identical. Cheeses produced with identical frozen culture and auxiliary Streptococcus thermophilus culture had more pronounced acidity before salting and lower after salting in comparison with cheeses with the mentioned two cultures. Organoleptic and other characteristics of mature cheeses were identical.